Developing Sapawarga As Value Orchestration Platform Using Service Science Perspective (Case Study Of West Java Provincial Government) - Aris Sandhika; Santi Novani (Journal of Social Research, 2025)
SAPAWARGA is part of the Jabar Super Apps initiative that created to improve access to public services in West Java by integrating multiple government services into one platform. Despite its potential, SAPAWARGA faces several challenges. First, user acquisition remains below its market potential, with only 2.82 million registered users as of 2024, a number that falls short of its estimated reachable market of 4 million users. Second, user engagement is low, with only 10.23% of registered users actively using the platform weekly. These issues highlight a disconnect between the platform’s offerings and the needs of its target audience. This research seeks to address these gaps by adopting a Service Science approach. Frameworks like Value Co-Creation and Value Orchestration Platform (VOP) are applied to explore strategies for aligning the platform with user expectations. In addition, the Customer Empathy Map is used to gain deeper insights into users' perspectives and refine the features of the platform to better meet their needs. Using qualitative methods such as interviews with users and service providers, this study presents actionable recommendations to improve SAPAWARGA. The recommendations include improving the platform's service design, encouraging stronger collaboration among stakeholders, and optimizing resource integration. By addressing these issues, SAPAWARGA can evolve into a more engaging and impactful digital public service solution, and realize its potential to serve West Java’s digitally savvy population.